PENGARUH PERPUTARAN MODAL KERJA DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA KOPERASI KARYAWAN BANK BUKOPIN PEKANBARU PERIODE 2012-2018 - Ferdian, Redho Refdi; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to partially and simultaneously examine the effect of Working Capital Turnover and Accounts Receivable Turnover on Profitability. Where the independent variables in this study are Working Capital Turnover and Accounts Receivable Turnover and the dependent variable is Profitabilty.Data analysis using simple linear regression analysis, multiple linear regression analysis, T test, F test and coefficient of determination test using SPSS 23.The results of the analysis show that Working Capital Turnover (t test) affects the value of Profitability on Bukopin Bank Employee Cooperative Pekanbaru, Accounts Receivable Turnover variables partially (t test) not affect the value of Profitability on Bukopin Bank Employee Cooperative Pekanbaru. Simultaneous test results (test f) show the influence of Working Capital Turnover and Accounts Receivable Turnover on Profitability at The Bukopin Bank Employee Cooperative Pekanbaru. Keywords: Working capital turnover, accounts receivable turnover, profitability